Recent flow analysis studies in vascular models using doppler ultrasound - Poepping, Tamie L.; Thorne, Meghan L.; Wong, Emily Y.; Rankin, Richard N.; Holdsworth, David W. (Canadian Acoustics, 2007)
Vascular disease is a major source of morbidity and mortality in Western society, with stroke and heart attacks accounting for about one third of deaths in North America. The carotid artery, and in particular the carotid bifurcation, is recognized as a common source of stroke-causing emboli that travel up into the brain, thereby blocking local blood flow. This has led to an emphasis on diagnostic techniques for assessing stroke risk due to carotid artery disease. Doppler ultrasound (DUS) techniques, in particular, uniquely enable visualization of flow patterns and characterization of various flow parameters. To improve our understanding of how blood-flow velocity patterns are modified as a result of disease in the carotid artery, basic research is typically carried out in physiologically realistic vascular models. In this paper, we review the progress that has been made in the development of ultrasound-compatible vascular models, as well as demonstrate the capabilities of DUS to quantify velocity patterns, turbulence, and recirculation. Ultrasound-compatible flow systems have been developed to mimic the geometry and hemodynamics of the carotid artery, under normal conditions and at various stages of narrowing due to atherosclerosis. These in vitro systems provide a controlled environment for developing new diagnostic techniques and for investigating and characterizing blood flow using DUS. Example data are shown from vessels with both eccentric and concentric stenoses, and in stenosed vessels that have been altered by the introduction of medical devices (stents) or additional roughness (ulceration). These results demonstrate the capacity for conventional clinical Doppler ultrasound devices to provide precise measurements of blood velocity from small sample volumes within a vessel, in order to build up detailed flow maps near and downstream of vascular disease or interventional device.